Sustained censorship in CA (2026-06) (Canada) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Canada. Data sourced from OONI.
Censorship Incident ID: CA-2026-0024. Severity: critical. Confidence: 85%